Change in Nurses’ Reactions to Psychosocial Work Environment Factors During the Accreditation Period - Reigas, Viljaras; Šukienė, Ingrida (Journal of Organizational Psychology, 2025)
In the modern healthcare system, significant focus is given to ensuring the quality of services, leading to the necessity of selecting the most suitable quality improvement measure for healthcare organizations. However, it has not been clear which quality improvement measure is the most appropriate for the healthcare services sector, as quality is understood and assessed differently in this field compared to other sectors. Various regulatory methods for healthcare service organizations are used worldwide, including licensing, accreditation, and certification. The application of quality assurance standards in healthcare organizations is based on the fact that these organizations seek to change their current practices to improve outcomes. Implementing each quality measure elicits certain reactions from healthcare professionals, which are not always favorable to the organization. This article examines the impact of accreditation on the changes in psychosocial work environment factors experienced by nurses during each accreditation phase.